The Relationship Between Future Time Perspective and Psychological Violence Among Chinese College Students - Zhi, Kuiyun; Yang, Jian; Chen, Yongjin; Akebaijiang, Niyazi; Liu, Meimei; Yang, Xiaofei; Zhang, Shurui (Frontiers in Psychology, 2021)
Based on early experiences and current conditions, a future time perspective influences college students’ behaviors, while psychological violence critically threatens college students’ health. This study explored the relationship between a future time perspective and the psychological violence of perpetrators based on an online investigation of 1424 college students (87.1% women) aged 17 to 31 in China. The results showed that a future time perspective is significantly positively associated with psychological violence. Positive future orientation is negatively associated with psychological violence. Negative and confused future orientations are positively associated with psychological violence. These findings support the need to introduce an intervention regarding a future time perspective to reduce psychological violence among college students.